2012
DOI: 10.1159/000342001
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Cerebral Connectivity Analysis in an Untreated Female-to-Male Transsexual Subject: A First Attempt Using Resting-State fMRI

Abstract: Background/Aims: Transsexualism is a gender identity disorder whose symptomatology could involve cognitive, neurobiological and psychological variance from biological sex standard. Several evidences support the hypothesis of a structural and functional brain reorganization in transgender subjects, with a different impact for male-to-female and female-to-male (FtM) subjects. Here we used resting-state fMRI to understand the similarities between the spontaneous brain connectivity of an untreated FtM subject and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
16
1
1
Order By: Relevance
“…The functional connectivity profile of an untreated FtM (who also had polycystic ovary syndrome) was more similar to female controls than to male controls (Santarnecchi et al, 2012). This study examined resting state fMRI, which means the participants were not involved in a task or activity while their brains were imaged.…”
Section: Connectivity Profilesmentioning
confidence: 99%
“…The functional connectivity profile of an untreated FtM (who also had polycystic ovary syndrome) was more similar to female controls than to male controls (Santarnecchi et al, 2012). This study examined resting state fMRI, which means the participants were not involved in a task or activity while their brains were imaged.…”
Section: Connectivity Profilesmentioning
confidence: 99%
“…As transsexuals exhibit sex-atypical anatomy in several brain regions (see paragraph "Brain morphometry"), knowing whether resting-state patterns of transsexuals resemble those of subjects with the same biological sex or rather those with the same gender identity is potentially meaningful. A future goal would be the creation of a connectivity profile of transsexual individuals and arranging it along the male/female-axis.As far as is known, there are two rsfMRI-studies with transsexuals, one bySantarnecchi, Vatti, Déttore and Rossi (2012) and one byLin and colleagues (2014).Santarnecchi and colleagues (2012) analysed resting-state brain connectivity in one untreated FtM transsexual individual and a male and female control group using both seed-and atlasbased analysis. The results suggest that the connectivity profile of FtM transsexuals is closer to subjects having the same biological sex rather than gender identity.…”
mentioning
confidence: 99%
“…Thus, our findings indicate that MtFs before hormonal treatment resemble their assigned, and not their aspired gender. This corroborates the only previous rs‐FC study in GD, which revealed greater similarity of an FtM individual with female control participants (Santarnecchi et al., 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Even less is known about differences in the RSN between individuals with GD and men and women. To the best of our knowledge, there is only one single‐case study comparing rs‐FC of one untreated FtM individual with samples of men and women, using seed‐voxel and atlas‐based region‐of‐interest approaches (Santarnecchi, Vatti, Dettore, & Rossi, 2012). In contrast to the aforementioned task‐related functional studies, this FtM revealed a stronger similarity to his biological as compared with his aspired gender in several predefined brain regions sensitive to gender dimorphism.…”
Section: Introductionmentioning
confidence: 99%